In vitro proliferation of mononucleated suspension and adherent cells from mouse and human peripheral blood system - Shahrul Hisham Zainal Ariffin,; Muhammad Dain Yazid,; Ruzanna Ab Kadir,; Shabnam Kermani,; Rohaya Megat Abdul Wahab, (Universiti Kebangsaan Malaysia, 2012)
Primary cells have a limited proliferative capacity with a finite number of times as compared with cell line which can grow indefinitely. Therefore, this study was carried out to identify the proliferative capacity of primary mononucleated cells from mouse and human. The mononucleated cells were isolated from mouse and human peripheral blood by density gradient centrifugation using Ficoll-Paque™ Plus. The two types of cells i.e. suspension and adherent forms were obtained after culturing the isolated mononucleated cells for 4 days in the complete medium consists of Alpha Minimal Essential Medium, 10% newborn calf serum and 2% penicillin/streptomycin. The cells were then cultured for another 10 days to observe cell viability using trypan blue exclusion assay (suspension form) and MTT assay (adherent form). NSO and MC3T3-E1 cell lines were selected as control cell for suspension and adherent cells, respectively. Our results showed that the proliferation rate of mouse suspension mononucleated cells increased from 1.31 ± 0.24 cells/day (day 5) to 2.69 ± 0.42 cells/day (day 10) whilst, for human suspension cells, the proliferation rate slightly increased from 0.56 ± 0.20 cells/day (day 5) to 0.76 ± 0.29 cells/day (day 10). However, the proliferation rate of mouse adherent mononucleated cells decreased from 0.23 ± 0.02 cells/day (day 5) to 0.17 ± 0.01 cells/day (day 10). Meanwhile, human adherent cells maintained proliferation rate at approximately 0.67 ± 0.18 cells/day. In conclusion, adherent primary mononucleated cells from both mouse and human have limited capacity to generate more cells in vitro as compared with suspension mononucleated cells.